How Short Video Content Marketing Could Trigger Purchase Intention of A Cosmeceutical Product Mediated By Brand Attitude - Natalia Sukarnadi; Ferdi Antonio (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aimed to test and analyze the effect of the elements of social media marketing (SMM), which consist of interesting content, scenario-based experience, user interaction, brand perception, and content invasiveness on brand attitude and their impact on purchase intention of cosmeceutical product with gender as moderation. To empirically test the proposed research model, a survey study with quantitative analysis was carried out. Data were obtained from consumers of a leading cosmeceutical product produced by a domestic company in Indonesia. Respondents were consumers who stated their plan to purchase cosmeceutical products and had seen short video content on the Instagram account. This research method is a quantitative survey. Respondent data was taken by purposive sampling with structural questionnaires distributed online. A total of 233 respondents were obtained that met the requirements for analysis with PLS-SEM. The results showed that the five elements of SMM as the content in social media, can significantly and positively influence brand attitude (b=0.05; CI 95%). A stronger effect was found on user interaction, followed by interesting content and brand perception. As expected, brand attitude demonstrated a positive impact on purchase intention while moderated by gender. The result indicates that SMM can trigger the purchase intention through interactive and interesting content. The findings of this study confirm that the female gender can strengthen the relationship between brand attitude and purchase intention. From the findings of this study, managerial implications can be drawn to assist the development of short video content in digital marketing of the cosmeceutical product, through Instagram.